(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The development of the internet in the 21st century has created new informational resources. However, students may readily access the internet connection. Since the internet is regarded as a vast informational resource, internet websites are crucial to our research and can serve as a tool for academic needs. The internet is helpful for quickly finding information and assisting students with their academic work, with just one search on the desired search engine. Nowadays, students choose to conduct online searches to get information. The information on the internet is easy to understand, beneficial, and believable. The use of credible internet resources is of greater importance. The internet may also be used as a resource to study the most recent news from around the globe and to obtain any kind of information for a variety of purposes. The researchers found that students are more satisfied with accessing the internet in terms of academic requirements and research sources. The study also revealed that students were "Highly satisfied" with the information they got from the internet. Internet access helps them finish their coursework easily. The researchers recommend practicing not being satisfied with one piece of information but rather searching for another source for comparison and checking reliability. Navigate needed information from different sources, and always check the review and ratings of a website and the context of the information. Always do fact-checking before gathering information.